Conceptualizing adolescents’ everyday stressors to underscore areas for support - Hellström, Lisa; Sjöman, Madeleine; Enskär, Karin (Frontiers in Education, 2024)
Identifying stressors in adolescents' everyday life may prevent future mental health problems and could be used to promote wellbeing in school. To be able to identify possible coping tools in a school setting, the aim of this study is to conceptualize adolescents' experiences of everyday stressors. Data was collected among 45 girls and 20 boys (aged 13-15) representing seven schools in Sweden. Participants were told to discuss everyday stressors in smaller groups and document important words/concepts. The documented notes were analyzed using a manifest linking process connected to domains and codes found in the International Classification of Functioning, Disability and Health (ICF) framework, following established linking rules. A total of 549 documented words/concepts connected to adolescents' experiences of daily stressors were collected and revealed stressor related to the ICF domains activities and participation (42.8%), body functions (30.1%) and environmental factors (27%). Regarding activities and participation, adolescents in the study perceived demands relating to school and social life as most stressful. The demands were put on them by themselves, parents, school, and society and were combined with a lack of time to handle the demands. Further, stressors related to how they are perceived by others and comparisons with peers were stressors connected to body functions. Stressors relating to environmental factors included derogatory attitudes and a lack of support, from parents and school as well as from peers. The results are discussed in terms of take-aways for school's health promotive work and potential coping tools for students.